Panji and Maritime Tradition: Representation of Panji in the Tradition of Pambelah Community - Prakosa, Rohmat Djoko (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2023)
This article examines the representation of Panji, a legendary hero in Javanese culture, in the maritime tradition of the Pambelah community. The Pambelah community, who live on the north coast of Java and work as fishermen, sailors, and boat builders, have a deep connection with the cosmic sea, the boat-making process, and the sailing activities. Through literature review and participant observation methods, this research explores the oral and written narratives of Panji about these activities. The findings reveal that Panji is not only a source of inspiration for various literary and artistic expressions but also a part of the spirituality and identity of the Pambelah community. They view Panji as a role model of kautaman (the highest level of human dignity) and mapan nyawiji (the merging of oneself with nature and God). In conclusion, the research on Panji in maritime tradition reveals the historical and cultural links between the agrarian and maritime aspects of Nusantara civilization and the dynamic and pluralistic nature of Panji culture.